Modernization of "Polimir" Process of High-Pressure Polyethylene Production at "Tomskneftekhim" Company; Advanced Materials Research; Vol. 560-561: Material Sciences and Technology - Klimov I. G.; Koval E. O.; Pestryakov A. N. Aleksey Nikolaevich; Mayer E. A. (2012, 2012)
Selected, peer reviewed papers from the 2012 Spring International Conference on Material Sciences and Technology (MST-S), May 27-30, 2012, Xi'an, China